No-Shave Long Hair Follicular Unit Excision Using an All-Purpose Skin-Responsive Device - Umar S; Khanna R; Gonzalez A; Chouhan K; Maldonado JC; Oguzoglu OT; Nusbaum A (Dove Medical Press, 2023)
Sanusi Umar,1– 3 Raveena Khanna,3,4 Alejandro Gonzalez,5 Kavish Chouhan,6 Juan Carlos Maldonado,7 Osman Tayfun Oguzoglu,8 Aron Nusbaum9 1Department of Medicine, Dermatology Division, University of California, Los Angeles, CA, USA; 2Division of Dermatology, Harbor-UCLA Medical Center, Torrance, CA, USA; 3Dr. U Hair and Skin Clinic, Manhattan Beach, CA, USA; 4Department of Dermatology, Howard University College of Medicine, Washington, DC, USA; 5Mxcapilar Clinic, Chulavista, Sonora, Mexico; 6Department of Dermatology, DermaClinix, New Delhi, India; 7Hair Evolution Robotics, Medellin, Colombia; 8Dr. T Hair Transplant, Istanbul, Turkey; 9Hair Transplant Institute, Miami, Coral Gables, FL, USACorrespondence: Sanusi Umar, Dr. U Hair and Skin Clinic, 2121 N Sepulveda Blvd, Suite 200, Manhattan Beach, CA, 90266, USA, Tel +1-310-480-0490, Fax +1-310-318-1590, Email drumar@dru.comBackground: Current no-shave long hair-follicular unit excision (LH-FUE) techniques employ recesses (slots, notches, or grooves) in punch tips to reduce the long-hair shaft break rate (SBR) and graft transection rate (GTR). However, these methods demand advanced skills and extended procedure time.Objective: We aimed to evaluate a skin-responsive FUE technique without the use of recess-tipped punches, accommodating diverse hair and skin types in LH-FUE procedures.Methods and Materials: We retrospectively analyzed patients who underwent this technique using a UGraft Zeus device at five multinational clinics (Mexico, Colombia, India, United States, and Türkiye) from August 9, 2021, to April 11, 2023. Donor zones were pre-operatively graded for expected difficulty using the Sanusi FUE Scoring (SFS) Scale, ranging from class I (low difficulty) to V (high difficulty).Results: Among 152 patients (mean age, 46 years; 146 straight-wavy, 6 curly-coiled hair), most (n=107) were class I donors. The GTR ranged 2.2%– 4.3%, and was highest in class IV donors and those with thick-firm scalps. The SBR was 12.2%, and the average graft excision rate (GER; speed) was 440 grafts/h. Only 19G and 18G punches were used. All patients were satisfied with the procedure, with 57.4% reporting that they were “very happy”. Surgeon willingness to perform no-shave LH-FUE significantly increased from 1.25 to 4.20 (on a scale of 1– 5) after adopting this device. SFS class, skin thickness, and firmness, more than hair curliness, influenced the GTR, SBR, torque, and punch movement duration.Conclusion: Our findings reveal consistent success in conducting no-shave LH-FUE using this skin-responsive device across diverse patients. Notably, success was achieved without recess-tipped punches, resulting in low GTR and SBR, along with a high GER and increased patient satisfaction. These outcomes suggest enhanced procedure speed and ease of use, contributing to a greater willingness among surgeons to adopt this technique.Plain Language Summary: Despite the increasing popularity of no-shave long-hair follicular unit excision (FUE) as a hair transplant technique for its advantages in preserving the donor area and immediately assessing results after implanting long hairs, its adoption by surgeons has been slow due to its demanding nature. It is time-consuming and skill-intensive because it requires specialized punches with recesses (slots, notches, or grooves) on their tips that must align to accommodate and protect the long hair shafts from breakage during each extraction.Our study reports a novel skin-responsive FUE device for performing nonshaven long-hair FUE called the UGraft Zeus, whose recess-free punch (The intelligent Punch) features a minimal-assist-navigation capability to simplify the procedure and enhances performance parameters, including speed, graft transection rate, hair shaft break rate, and its easy adoption rate by surgeons, including novices. Additionally, patient satisfaction is high.Additionally, skin characteristics, specifically thickness and firmness, play a more critical role than the degree of hair curliness. Thicker and firmer skin requires increased torque and a longer punch movement duration during surgery. Furthermore, the skin-responsive FUE device was successful in performing no-shave long hair FUE in patients with Afro-textured hair, a population typically considered to be a hair transplant challenge.Keywords: follicular unit extraction, nonshaven FUE, unshaven FUE, long-hair FUE, hair transplantation, hair restoration surgery